Parental styles and risk factors associated with eating pathology - Marmo, Julieta (2014)
This review intends to describe Eating Disorders*(ED) and its relationship with Risk Factors (RF) and Parental Styles (PS). EDs are alterations related to intake, weight and body image.PSs are upbringing guidelines that refer to the modality in which socialization norms are given. RFs are events that predispose a subject to suffer a mismatch. A critical analysis and theoretical systematization on current research was conducted. The findings indicate that EDs occur within a dysfunctional family where no PS exclusively excels, and where risk factors associated with eating pathology can be warned.